Artificial intelligence application for museum to experiential transformation of cultural heritage and learning - İslam Suiçmez; Fahriye Altinay; Gökmen Dağlı; Haijun Zeng; Rustam Shadiev; Didem İşlek; İpek Danju; Zehra Altinay (Smart Learning Environments)
Abstract This study aims to explore the contributions of artificial intelligence (AI) applications in museums to the accessibility, interaction, and experiential transformation of cultural heritage. AI accelerates digital transformation in museums, enhancing visitor experiences by making them more interactive and personalized, while also aiding in the preservation and dissemination of cultural heritage. Designed as a qualitative research project, the study will employ descriptive content analysis. Participants will consist of a total of 110 university students from Kazakhstan, Korea, China, Turkey, the Turkish Republic of Northern Cyprus, and India. Data will be collected through semi-structured interview forms and analyzed using QDA Miner Lite software. This research broadly examines the integration of artificial intelligence into museums. It aims to investigate how AI-supported museum applications contribute to access to cultural heritage from the past to present, enhance museum experiences for civilizations and individuals from various cultural backgrounds, and make them more engaging and interactive. Additionally, it explores the effects of the digitization of cultural identity and heritage on individuals and the innovations AI brings to museum education and information processes. The primary objective of this research is to raise awareness about AI-supported museum applications and to emphasize the significance of the connection between technology and cultural heritage. Additionally, it aims to demonstrate the impact of artificial intelligence on the preservation and transmission of cultural heritage to future generations. In line with this expectation, it is anticipated that future studies will further integrate AI-supported applications into museums, thereby facilitating and enhancing the preservation and transmission of cultural heritage. The findings of this research provide evidence supporting this expectation. In light of these aspects, the study seeks to present projections and recommendations for the future of AI-supported museology.